A novel extracellular low‐temperature active phytase from Bacillus aryabhattai RS1 with potential application in plant growth. (20th March 2017) - Pal Roy, Moushree; Datta, Subhabrata; Ghosh, Shilpi
Abstract : Bacillus aryabhattai RS1 isolated from rhizosphere produced an extracellular, low temperature active phytase. The cultural conditions for enzyme production were optimized to obtain 35 U mL −1 of activity. Purified phytase had specific activity and molecular weight of 72.97 U mg −1 and ∼40 kDa, respectively. The enzyme was optimally active at pH 6.5 and 40°C and was highly specific to phytate. It exhibited higher catalytic activity at low temperature, retaining over 40% activity at 10°C. Phytase was more thermostable in presence of Ca 2+ ion and retained 100% residual activity on preincubation at 20–50°C for 30 min. Partial phytase encoding gene, phyB (816 bp) was cloned and sequenced. The encoded amino acid sequence (272 aa) contained two conserved motifs, DA[A/T/E]DDPA[I/L/V]W and NN[V/I]D[I/L/V]R[Y/D/Q] of β‐propellar phytase and had lower sequence homology with other Bacillus phytases, indicating its novelty. Phytase and the bacterial inoculum were effective in improving germination and growth of chickpea seedlings under phosphate limiting condition. Moreover, the potential applications of the enzyme with relatively high activity at lower temperatures (20–30°C) could also be extended to aquaculture and food processing. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:633–641, 2017